RAGAM BAHASA PADA PODCAST YOUTUBE DENNY SUMARGO “PANDAWARA GROUP” - Kiki Reski Wulandari; Ita Ita (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2026)
This research aims to identify the language varietied that exist in Denny Sumargo’s YouTube Podcast with Pandawara Group guest stars. This research is a type of field research. The method used is descriptive qualitative. The object of this research is Denny Sumargo’s YouTube Podcast. The data collection techniques and note-taking techniques. From the results of data analysis, researchers found several language varieties in Denny Sumargo’s YouTube Podcast with Pandawara Group guest stars, namely colloquial, dialect, spoken and familiar language varieties. The number of colloquial language varieties is:9. dialect language:2, familiar language varities:3 and official variety 2.